An activated c-Ha-ras allele blocks the induction of muscle-specific genes whose expression is contingent on mitogen withdrawal. - Payne, P A (1987)
During myogenesis, induction of muscle-specific genes is subject to negative control by polypeptide mitogens and type-beta transforming growth factor. Since transduction of growth factor signals may require proteins encoded by cellular ras oncogenes, we have tested whether a mutationally altered Harvey ras expression vector, by itself, can prevent establishment of a differentiated phenotype in BC3H1 mouse myoblasts. Transfection with the valine-12 allele of the human Harvey ras gene, under the control of its own promoter, was sufficient to prevent the induction of both muscle creatine kinase activity and the nicotinic acetylcholine receptor following mitogen withdrawal but did not inhibit withdrawal from the cell cycle. The loss of creatine kinase activity resulted from a corresponding block to induction of muscle creatine kinase mRNA. Similarly, mitogen withdrawal elicited little or no alpha-actin mRNA in ras-transfected cells. These results suggest that an activated ras allele can inhibit myogenesis through a mechanism independent of cell proliferation and can preclude activation of genes whose up-regulation normally accompanies mitogen withdrawal.